1998
DOI: 10.1117/12.327201
|View full text |Cite
|
Sign up to set email alerts
|

Polarization diversity active imaging

Abstract: We present the concept of a Polarization Diversity Active Imager operating at ? = 810 rim. Each pixel of the image is encoded by the polarization degree Pd (0% < Pd < 100%) given by its Mueller Matrix. The measurement of the Mueller matrices is obtained using the Dual Rotation Retarder Technique (DRRT). A theoretical analysis and an experimental validation of this technique are presented. The device is operating in a monostatic configuration, using a semiconductor laser (X = 810 tim) to illuminate the target a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…So we can get four different polarization images of the same scene on two detectors at the same time 3 . …”
Section: Polarization Information Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…So we can get four different polarization images of the same scene on two detectors at the same time 3 . …”
Section: Polarization Information Processingmentioning
confidence: 99%
“…It increases the amount of information of the detected scene. Various technological approaches of imaging polarimeters have been studied [1][2][3][4][5][6][7][8] . We have designed a simultaneous imaging polarimetry with double separate Wollaston Prism(SIP-DSWP) 9-10 , which is a combination of division-of-amplitude and division-of-aperture.…”
Section: Introductionmentioning
confidence: 99%
“…The most general and widely used formulism of imaging polarimetry is the SVI (5)(6)(7)(8)(9)(10)(11)(12) . In the SVI representation the polarization properties of the electromagnetic radiation can be completely described by the Stokes vector imagery S I that consists of four images known as the Stokes images:…”
Section: Imaging Polarimetry and Stokes Vector Imagerymentioning
confidence: 99%
“…S 1 , S 2 , and S 3 , images, respectively describes linear polarization, orientation, and circular polarization content of light in the scene. SVI can be determined using a time-sequential intensity measurement approach (5)(6)(7)(8) as in the following arrangement: Other useful images may be obtained using a combination of SVI elements: the degree of linear polarization DLP is a measure of the amount of linear polarization defined as:…”
Section: Imaging Polarimetry and Stokes Vector Imagerymentioning
confidence: 99%
“…It has been showed that DOLP imaging is a powerful tool to detect man made objects [8][9][10][11] . Manmade objects are usually associated with a higher DOLP than natural objects.…”
Section: Target Detection Contrast Enhancementmentioning
confidence: 99%